Continuity of care (COC) With Labor Pain and Breast Milk That Has Not Been Out In The Public Period - Falina, Chrysa; Utami, Iis Tri; Handayanti, Riyani; Susanti, Yenni (JKM (Jurnal Kebidanan Malahayati), 2024)
ABSTRACT: Continuity of care (COC) With Labor Pain and Breast Milk That Has Not Been Out In The Public Period Continuity of care (COC) is an effort to provide continuous care starting from pregnancy, childbirth, postpartum, newborns, and family planning. This care aims to monitor the condition of mothers and babies as an effort to reduce maternal mortality rates and infant mortality rates. This research design uses a descriptive method using a case study approach carried out by providing comprehensive midwifery care. A case study is research carried out by examining a problem through a case consisting of a single unit. Based on the results of the subjective data and objective data analysis, Mrs. N, 25 years old, G1P0A0, 37 weeks pregnant, intrauterine single fetus, cephalic presentation. 1. After reviewing subjective, objective and supporting data using a comprehensive approach and SOAP documentation on Mrs. N it can be concluded that the respondent was in good condition during pregnancy, childbirth, postpartum and family planning, and the respondent's baby was also in good condition. Keywords: Pregnancy, Continuity of care, Postpartum Period